Two modifications of layered cobaltous terephthalate: Crystal structures and magnetic properties - Kurmoo, M; Kumagai, H; Green, M; Lovett, B; Blundell, S; Ardavan, A; Singleton, J (2001)
The synthesis, characterization, crystal structure, and magnetic properties of Co2(OH)2BDC and Co(H2O)2BDC (BDC is benzene 1,4-dicarboxylate or terephthalate, O2CC6H4CO2) are reported. Co2(OH)2BDC (C2/m, a=19.952, b=3.286, c=6.295 Å, β=95.84°, Z=2, V=410.6 Å3) consists of two types of edge-sharing CoO6 chains that are connected to each other by OH (Co-O-Co bridges) to form layers that are further joined together through terephthalate. It exhibits unusual magnetic properties: above 48 K it displays paramagnetism, between 44 and 48 K it behaves as a collinear antiferromagnet, and below 44 K a weak spontaneous magnetization is observed in very low applied fields. At higher fields metamagnetic behavior is observed. Two types of hysteresis loops are observed, one centered about zero field and the second about the metamagnetic critical field. The critical field and the hysteresis width increase as the temperature is lowered; the latter exceeds 50 kOe at 2 K. The unusual large coercivity may be due to the large single-ion anisotropy of Co(II) and its pronounced increase at low temperature. Co(H2O)2BDC (C2/c, a=18.274, b=6.543, c=7.296 Å, β=98.6°, Z=4, V=862.5 Å3) consists of layers of separated octahedral CoO6 connected via Co-O-C-O-Co. It is paramagnetic and obeys the Curie-Weiss law (Θ=-27 K). © 2001 Academic Press.